Upaya Dinas Kebudayaan Dan Pariwisata Mempromosikan Mesjid Raya Pulau Penyengat Sebagai Daerah Tujuan Wisata di Tanjung Pinang Kepulauan Riau - Syaiful, Sefrona; Syech, Achmad (Jurnal Daya Saing, 2015)
Abstract: Efforts to make the Masjid Raya Island Biting as an object of religious tourism in the province of Riau Islands, has been carried out by the manager and local governments, among others, the promotion to both domestic and international travelers is done so that the level of tourists who come can be as expected , Promotional efforts undertaken by the Department of Culture and Tourism in increasing the number of visits such as: the availability of tourism information center, stinger island festival, held in cooperation with travel agencies and increased advertising on the island stinger. And the presence of Culture and Tourism today can say is good. With various promotions conducted by the relevant authorities so that the future can increase traffic. The potential for developing tourism on the island Biting the moment is religious tourism and historical tourism and culture Keywords: Promotion, Mesjid Raya, Religious Tourism